Bank Insolvency and Stabilization in Eastern Europe. (IMF Working Papers; Working Paper ;, 1992)
The profound structural reform underway in Eastern Europe has revealed the weakness of the banking sector there; macroeconomic stability and other reforms are thereby threatened. After an overview of recent developments in the banking sectors of these countries, a model is developed that clarifies the role of banking in an emerging market economy, and the danger that the disturbances inherent to it may be magnified and prolonged by a banking collapse. The implication is that priority must be given to mobilizing fiscal resources to cover the costs of restructuring the banking sector.